2021
DOI: 10.1088/1742-6596/1898/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of IoT based Automated Tomato Watering System Using ESP8266

Abstract: Tomatoes need a proper watering system in order to grow and provide optimal yields. The factors that must be considered in watering the tomatoes are soil moisture and air temperature. The soil moisture needed for planting tomatoes is between 60% to 80% with a temperature rate between 24 to 28 degrees Celsius. We propose to implement an IoT based agricultural technology innovation to address the problem of precise watering system based on soil moisture and air temperature rate, which can be controlled remotely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The test results of the smart greenhouse are presented in Table 1. The findings revealed that the heating and watering of greenhouse crops can be done through automation and smart process, which is further confirmation of the researches carried out by Goap et al (2018) and Nurhasanah et al (2021). The increment observed in the greenhouse air temperature during the test running period can be linked to the external atmospheric conditions.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The test results of the smart greenhouse are presented in Table 1. The findings revealed that the heating and watering of greenhouse crops can be done through automation and smart process, which is further confirmation of the researches carried out by Goap et al (2018) and Nurhasanah et al (2021). The increment observed in the greenhouse air temperature during the test running period can be linked to the external atmospheric conditions.…”
Section: Resultssupporting
confidence: 76%
“…The temperature, soil moisture content and soil nutrient level of the greenhouse environment will be programmed according to the environmental requirement of the intended planted crop inside the greenhouse. According to Nurhasanah et al (2021) reports, most vegetables and fruits require soil moisture content that ranges from 60% to 80% and environmental temperature that ranges from 240°C to 300°C. Environmental conditions outside the optimal range of a crop severely affect its production and performance (Ma et al, 2016;Xue et al, 2017;Awad et al, 2022).…”
Section: Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous solutions have been developed to help the farmers improve the plant watering process [4]- [6]. Nurhasanah et al propose implementing an IoT-based agricultural technology innovation to address the problem of a precise watering system for tomato plants [7]. Codeluppi [8] presented lowcost and modular IoT solutions for monitoring and controlling vegetable plants.…”
Section: Introductionmentioning
confidence: 99%
“…The data is also used to manage the plant watering and fertilization processes. rate, which can be controlled remotely via an internet connection [5]. Hicham Megnafi et al developed a solarpowered watering system that measures soil humidity and ambient temperature to determine optimal watering conditions [6].…”
Section: Introductionmentioning
confidence: 99%